Components of Rice Field Ecosystems as a Source of Biology in High School in Dompu District in 2020 - Ulfin Juwita; Agil Al Idrus; Mahrus Mahrus (Jurnal Biologi Tropis, 2022)
Rice fields as an ecosystem have two main components, namely abiotic and biotic with the main function of ensuring the survival of organisms and creating a balanced ecosystem. Ecosystem components in an environment can be used as a source of learning Biology. This study aims to find out what are the components of the rice field ecosystem in Indonesia Dompu Regency and assess the characteristics or criteria of ecosystem components rice fields as a source of high school biology learning in Dompu Regency with refers to the 2013 curriculum. This type of research is descriptive exploratory. This research was conducted in Kempo Village, Dompu Regency at 4 points sampling, namely: transect 1 (North), transect 2 (West), transect 3 (South) and transect 4 (East). The sampling technique uses the method square. Collecting data using observation sheets and documentation. The results showed that the biotic component consisted of 15 species and 20192 individuals and the number of abiotic components as many as 5 environmental factors. Mark the average learning resource criteria ( ) for all transects is 3.4 (Category Very Meets the Criteria (SMK) learning resources). Research result concluded that the biotic component consisted of 15 species including Paddy (Oryza sativa), Bamboo grass (Lophatherum gracile), grinting grass (Cynodon dactylon), Patikan kebo (Euphorbia hirta), Earrings (Acalypha australis), Meniran (Phyllanthus urinaria), Urang-aring (Eclipta prostrata), Beluntas (Pluchea indica), Jotang horse (Synedrella nodiflora L.), Ciplukan (Physalis angulata L.), Cucumber (Coccinia grandis), Purslane (Portulaca oleracecea L.), Basil (Ocimum sanctum), Koksi beetle (Epilachna admirabilis) and earthworms (Lumbricus rubellus), while the components of Abiotic consists of 5 elements including temperature, humidity, pH of water, water and soil. The components of the rice field ecosystem in Dompu Regency can be used as high school biology learning resources in the sub-material component of the curriculum ecosystem 2013 with an average value of 3.4 learning resource criteria.